Antibody biosensors for the measurement and characterization of soluble CD147 molecules - Witida Laopajon (2018)
BACKGROUND: Soluble CD147 (sCD147) is the shed form of membrane-bound CD147, which is involved in the regulation of cellular functions. The presence of sCD147 in body fluids is associated with several diseases.OBJECTIVE: In this study, we aimed to establish antibody (Ab) biosensors for the simultaneous differential detection of the general and truncated forms of sCD147.METHOD: By combining biolayer interferometry technology (BLItz) and different anti-CD147 monoclonal antibodies (mAbs) specific to different extracellular domains of the CD147 molecule, Ab-based biosensors were established to rapidly measure and characterize sCD147 isoforms.RESULTS: Two types of Ab-biosensors, desginated the single Ab-biosensor and double Ab-biosensor, were established for the measurment and characterization of sCD147 isoforms. For the single Ab-biosensor system, monoclonal antibodies specific for CD147 domain 1 (D1) or domain 2 (D2) were immobilized on the sensor tips and used for the quantification of sCD147 using a BLItz optical interferometric biosensor. For the double Ab-biosensor system, following the single Ab-biosensor step, secondary anti-CD147 mAbs specific for each domain of the CD147 molecule were added and monitored by a BLItz biosensor. By combining the results obtained from the single Ab- and double Ab-biosensors, sCD147 isoforms including the general form (D1 linked to D2) and the truncated forms (sCD147 containing D1 or D2) could be determined.CONCLUSIONS: This method may be a beneficial tool for the determination of sCD147 isoforms for disease diagnosis and prognosis as well as for the definition of the cellular mechanisms of the immune system.